Using Community of Inquiry (CoI) to Facilitate the Design of a Holistic E-Learning Experience for Students with Visual Impairments - Sindile A. Ngubane-Mokiwa; Simon Bheki Khoza (MDPI AG, 2021)
Information and Communication Technology (ICT) tools provide an ideal mechanism by which students can interact closely with their lecturers in an open distance learning (ODL) context. This is especially true for students with disabilities who require access through alternative formats. This paper demonstrates teaching and learning practices in an ODL institution in South Africa, with a focus on the indispensable role of lecturers and tutors in an online learning setting. The paper employs the Community of Inquiry, which sees the effective online learning environment through three elements: cognitive, social, and teaching presence. The findings shed light on the use of vision-based approaches in course design; limited implementation of open-access policies, and the academic faculty's lack of knowledge on how to facilitate inclusive learning. The paper concludes by presenting a proposed student-centred framework that seeks to facilitate inclusive teaching and learning towards positive and inclusive learning experiences for students. The proposed framework could be beneficial during pandemic situations.